(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
Critical review of species composition of the genus Leveillula in Ukraine is presented. L. contractirostris Heluta et Simonian, L. cylindrospora U. Braun, L. duriaei (Lév.) U. Braun, L. helichrysi Heluta et Simonian, L. lactucarum Durrieu et Rostam, L. taurica (Lév.) G. Arnaud, and L. verbasci (Jacz.) Golovin are recorded for the territory. Furthermore, a number of specimens turned out to be Leveillula sp. (L. scolymi (Prost) Durrieu et Rostam, nom. inval.) or were not identified to the species level. The key for identification of presented species and maps of their distribution in Ukraine are given. It is concluded that the boundary of natural habitat of the genus Leveillula follows the territory of Ukraine.